Impact of Social, Economic, and Healthcare Factors on the Regional Structure of Antibiotic Consumption in Primary Care in Poland (2013–2017) - Olczak-Pieńkowska, Anna; Hryniewicz, Waleria (Frontiers in Public Health, 2021)
Antibiotic resistance is one of the most important public health threats worldwide. Antimicrobial misuse and overuse are well recognized risk factors for the resistance emergence and spread. Monitoring of antibiotic consumption (AC) is an important element in strategies to combat antibiotic resistance. As a result of AC surveillance in Poland the regional differences in AC levels were observed. The aim of the study was to characterize the regional AC in 2013-2017 in primary care in Poland and assess possible determinants that influence the AC at the regional level. The study analyzed relationships between AC and its factors (grouped in 3 different categories: demographic, economic, and related to the organization of healthcare). Data covered AC in primary care in five years period (2013-2017) from all 16 Polish voivodeships. The strongest correlation was demonstrated with factors related to the employment, female reproductive activity, mobility of the population, the number of outpatient consultations, and the number of dentists. Correlation was also found with population mobility and density. Recognized risk factors for increased consumption of antibiotics should be a priority for interventions implementing and disseminating rational antibiotic policy.